Pengaruh Kualitas Pelayanan dan Tingkat Penghasilan Terhadap Kepatuhan Membayar Pajak Kendaraan Bermotor di Kabupaten Klungkung - Purnadewi, Ni Kadek Wahyu; Suwena, Kadek Rai (Jurnal Pendidikan Ekonomi Undiksha, 2023)
The purpose of this study was to determine the relationship between service quality and income level on compliance with paying motor vehicle taxes in Klungkung Regency. This research uses causal research. The population in this study is Klungkung regency motor vehicle taxpayers, totaling 109,276 people in 2020. The sampling technique used in this study is simple random sampling, so the number of samples used after being calculated by the Slovin formula is 399 people. The data collection method used is a questionnaire. The data analysis techniques used are multiple linear regression analysis, t-test, and F-test. The results showed that there was a partial and simultaneous effect of service quality and income level on compliance with paying motor vehicle taxes in Klungkung Regency.